Alcohol and energy drinks: a pilot study exploring patterns of consumption, social contexts, benefits and harms - Pennay Amy; Lubman Dan I (BMC Research Notes, 2012)
Abstract Background Young people around the world are increasingly combining alcohol with energy drinks (AEDs). However, as yet, limited research has been conducted examining this issue, particularly in terms of exploring patterns of consumption, social practices and the cultural contexts of AED consumption. We sought to understand how AEDs are used and socially constructed among young people. Methods We conducted 25 hours of observation in a variety of pubs, bars and nightclubs, as well as in-depth interviews with ten young people who regularly consumed AEDs during a session of alcohol use. Results In this pilot study, participants were highly organised in their AED consumption practices and reported rarely altering this routine. Some young people consumed upwards of eight AEDs on a typical night, and others limited their use to between three and five AEDs to avoid unpleasant consequences, such as sleep disturbances, severe hangovers, heart palpitations and agitation. Wakefulness and increased energy were identified as the primary benefits of AEDs, with taste, reduced and increased intoxication, and sociability reported as additional benefits. Young AED users were brand sensitive and responded strongly to Red Bull imagery, as well as discounted AEDs. Finally, some young people reported substituting illicit stimulants with energy drinks. Conclusions Combining energy drinks with alcohol is now a normalised phenomenon and an integral and ingrained feature of the night-time economy. Despite this, many young people are unaware of recommended daily limits or related harms. While some young people consume AEDs to feel less drunk (consistent with motivations for combining alcohol with illicit stimulants), others report using AEDs to facilitate intoxication. While preliminary, our findings have relevance for potential policy and regulatory approaches, as well as directions for future research.